Composition for vehicle wheel member, and molded body and wheel balancer using same
By using a composition of thermoplastic polyurethane, plasticizer, and metal particles, the problem of easy corrosion and cracking of wheel balance blocks in high-temperature and corrosive environments was solved, achieving excellent adhesion and durability, and reducing the wheel balance error rate.
Patent Information
- Application Number
- CN202411753932.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-31
- Filing Date
- 2024-12-02
- Publication Date
- 2026-02-10
AI Technical Summary
Existing wheel balance weights are prone to corrosion and peeling in high-temperature and corrosive environments, and are also prone to cracking under bending fatigue conditions, making it difficult to achieve excellent adhesion and durability.
A composition comprising thermoplastic polyurethane, plasticizer, and metal particles is used to form a molded body by extrusion molding, ensuring that the composition has a density of 3 g/cm3 or greater and a Shore A hardness of 59 to 92, enhancing adhesion and durability.
It achieves crack-free operation under repeated bending conditions, exhibits excellent corrosion resistance and weather resistance, reduces wheel balance error rate, and improves productivity and durability.
Smart Images

Figure CN121491330A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a composition for a vehicle wheel member and a molded body and a wheel balance weight using the same. BACKGROUND
[0002] A wheel balance weight can be provided to correct weight imbalance in a wheel, a rim, etc. of a vehicle. These wheel balance weights can generally include steel, but corrosion can occur under environmental conditions exposed to a wheel, high-temperature water inflow conditions, winter calcium chloride inflow conditions, etc. In addition, peeling and lifting can occur due to poor adhesion to a curved surface of a wheel. Also, difficult precision control can result in excessive wheel balance defects. Furthermore, such wheel balance weights can be susceptible to breakage during a manufacturing process due to insufficient fatigue resistance under repeated bending conditions.
[0003] Wheel balance weights to which a composition mainly containing a polyester resin is applied are problematic in that productivity is deteriorated due to insufficient repeated bending fatigue properties and also because cracking or breakage often occurs during production and application of a molded body.
[0004] The statements in the background section merely provide background information related to the present disclosure and can not constitute prior art. SUMMARY
[0005] The present disclosure is directed to solving problems encountered in the related art. An object of the present disclosure is to provide a composition and a molded body having excellent adhesion to a curved surface of a vehicle wheel and easy moldability.
[0006] Another object of the present disclosure is to provide a composition having fatigue resistance against repeated bending that can occur during manufacturing or balancing operations of a product and capable of exhibiting excellent durability and a low wheel balance error rate.
[0007] The objects of the present disclosure are not limited to the foregoing. The objects of the present disclosure should be more clearly understood through the following description.
[0008] An aspect of the present disclosure provides a composition for a vehicle wheel member, the composition including 100 parts by weight of a thermoplastic polyurethane, 1 to 30 parts by weight of a plasticizer, and 400 to 1,680 parts by weight of metal particles, wherein the composition can have a density equal to or greater than 3 g / cm 3 and the thermoplastic polyurethane can have a Shore A hardness in the range of 59 to 92.
[0009] Another aspect of the present disclosure provides a molded body comprising a thermoplastic polyurethane, metal particles in an amount ranging from 400 to 1,680 parts by weight based on 100 parts by weight of the thermoplastic polyurethane, and a plasticizer, wherein the molded body can have a density equal to or greater than 3.2 g / cm 3 and the thermoplastic polyurethane can have a Shore A hardness in the range of 59 to 92. BRIEF DESCRIPTION OF DRAWINGS
[0010] The above and other features of the present disclosure are described in detail below with reference to embodiments of the present disclosure illustrated in the accompanying drawings, which are given by way of illustration only and thus are not restrictive of the present disclosure, and wherein:
[0011] Figure 1 is a photo of a wheel balance block to which a molded body according to an embodiment of the present disclosure is applied and to which a film is attached;
[0012] Figure 2 is a photo schematically showing a bending fatigue resistance test procedure described in Test Examples;
[0013] Figure 3 is a photo showing results after a bending fatigue resistance test of some embodiments described in Test Examples; and
[0014] Figure 4 is a photo showing results after a hydrolysis resistance test of Reference Example 6 described in Test Examples. DETAILED DESCRIPTION
[0015] The above and other objects, features and advantages of the present disclosure will be more clearly understood from the following detailed description taken in conjunction with the accompanying drawings, although the present disclosure is not limited thereto. The following embodiments are provided so as to fully convey the spirit of the present disclosure to one of ordinary skill in the art. Embodiments of the present disclosure are described in detail with reference to the drawings.
[0016] Throughout the drawings, like reference numerals will be used to designate like or similar elements. For the sake of brevity of description with regard to the clarity of the present disclosure, the size of structures is exaggerated relative to other elements. It should be understood that although terms such as "first", "second", and the like can be used herein to describe various elements, these elements are not limited by these terms. These terms are only used to distinguish one element from another. For example, a "first" element discussed below can be termed a "second" element without departing from the scope of the present disclosure. Similarly, a "second" element can also be termed a "first" element. As used herein, the singular forms are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0017] It will also be understood that, when used in this specification, the terms "comprise", "contain" and "have", and the verb "comprising", "containing" and "having", shall be taken to express the inclusion of the stated features, integers, steps, operations, elements, components or groups thereof, but not the exclusion of one or more other features, integers, steps, operations, elements, components or groups thereof. Furthermore, it shall be understood that the use of the term "about" in relation to a given value shall be taken to mean that the value is within a range of ±10% of the given value. Moreover, it shall be understood that when an element such as a layer, film, region or sheet is referred to as being "on" another element, this can also mean that there are intervening elements present.
[0018] Unless otherwise specified, all numerical values, values and / or expressions representing quantities of components, reaction conditions, polymer compositions, and mixtures used herein are to be understood as modified by the term "about", including the inherent variations of the measurement as determined by the equipment used for making the measurement and, therefore, are understood to be preceded by the term "about". Furthermore, when disclosing numerical ranges, the range is continuous, and includes all values from the lower value to the higher value, unless otherwise indicated. Furthermore, when such a range is disclosed to include integers, the integers include all integers within the range, unless otherwise indicated.
[0019] In this disclosure, each of the phrases "A or B," "at least one of A and B," "at least one of A or B," "A, B, or C," "at least one of A, B, and C," "at least one of A, B, or C," and "at least one of A, B, or C, or a combination thereof" can include any one or all possible combinations of the items listed together in the corresponding one of the phrases.
[0020] Composition for vehicle wheel member
[0021] One aspect of the present disclosure relates to a composition for a vehicle wheel member. The composition for a vehicle wheel member comprises:
[0022] 100 parts by weight of a thermoplastic polyurethane,
[0023] 1 to 30 parts by weight of a plasticizer; and
[0024] 400 to 1,680 parts by weight of metal particles.
[0025] The composition can have a density of 3 g / cm 3 or more, and the thermoplastic polyurethane can have a Shore A hardness of 59 to 92.
[0026] The vehicle wheel member can be a wheel balance weight, can be a member applied to adjust the wheel balance of a vehicle, can be a member attached to a part such as a wheel, a rim of a wheel, etc., and can be attached to a curved portion.
[0027] Further, in addition to the vehicle wheel member, the composition can be applied to a wheel member of other transportation means, and can be applied as a composition required for a member or a part other than a wheel member, which requires similar properties such as bending fatigue resistance, weather resistance, corrosion resistance, adhesion.
[0028] The thermoplastic polyurethane (TPU) can be a thermoplastic elastomer having a predetermined elasticity. The thermoplastic elastomer can be obtained by reacting A-1) at least one of a polyester polyol, a polyether polyol, or a combination thereof, A-2) a diisocyanate-based compound, A-3) a compound containing hydrogen and an acid functional group capable of reacting with an isocyanate, A-4) a siloxane-based compound containing a hydroxyl group, A-5) a silane coupling agent, and A-6) a crosslinking agent.
[0029] For example, the thermoplastic polyurethane elastomer can be prepared by reacting a composition for producing a TPU in the presence of 0.01 to 1 parts by weight of a catalyst, the composition comprising:
[0030] A-1) 100 parts by weight of at least one polyol of a polyester polyol, a polyether polyol, or a combination thereof,
[0031] A-2) 20 to 50 parts by weight of a diisocyanate-based compound,
[0032] A-3) 2 to 15 parts by weight of a compound containing hydrogen and an acid functional group capable of reacting with an isocyanate,
[0033] A-4) 1 to 10 parts by weight of a siloxane-based compound containing a hydroxyl group,
[0034] A-5) 0.3 to 5 parts by weight of a silane coupling agent, and
[0035] A-6) 2 to 20 parts by weight of a crosslinking agent.
[0036] The number average molecular weight of the polyol of A-1) can be 2,500 g / mol to 4,000 g / mol.
[0037] In A-1), the polyether polyol can be obtained by reacting an alkylene oxide such as ethylene oxide, propylene oxide, etc. with a polyhydroxy alkane or an amine compound. Examples of the hydroxy alkane can include diols such as ethylene glycol, propylene glycol, etc., and triols such as glycerol, trimethylolpropane, etc. Examples of the amine compound can include ammonia, triethanolamine, ethylenediamine, etc.
[0038] In A-1), polyols and polyester polyols can be obtained by reacting a dicarboxylic acid with at least one diol. Examples of dicarboxylic acids may include aliphatic dicarboxylic acids such as adipic acid, glutaric acid, azelaic acid, and sebacic acid, and aromatic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthenic acids. Examples of diols may include diols such as ethylene glycol, 1,2-propanediol, diethylene glycol, 1,4-butanediol, and 1,6-hexanediol, and polyols such as glycerol, trimethylolpropane, and pentaerythritol.
[0039] A-2) Examples of diisocyanate compounds may include toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylene diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene-1,5-diisocyanate (NDI), isophorone diisocyanate (IPDI), cyclohexyl diisocyanate (CHDI), hexamethylene diisocyanate, etc.
[0040] Examples of compounds containing hydrogen and acidic functional groups capable of reacting with isocyanates may include N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid, 2,2-bis(hydroxymethyl)butyric acid, 2,2-bis(hydroxymethyl)valerate, 2,2-bis(hydroxymethyl)hexanoic acid, 3,5-diamino-4-methylbenzoic acid, 4,4-diamino(1,1-diphenyl)-2,2-disulfonic acid, 4,6-diaminobenzene-1,3-disulfonic acid, 4,4-diamino-2,2-stilbenesulfonic acid, dihydrolipoic acid, etc.
[0041] Furthermore, compounds containing hydrogen and acidic functional groups capable of reacting with isocyanates (A-3) can include compounds neutralized with a neutralizing agent, and amine compounds can be used as neutralizing agents. Examples of amine compounds include butylamine, 3-amino-1,2,4-triazole, (2-methylbutyl)amine, 5-cyclopropyl-1,3,4-oxadiazole-2-amine, dodecylamine, cyclohexylamine, etc.
[0042] (A-4) Hydroxyl-containing siloxane compounds can be hydroxyl-containing polydimethylsiloxanes (PDMS) and can have a hydroxyl value of 20 mg KOH / g to 100 mg KOH / g.
[0043] (A-5) Silane coupling agents can be silane coupling agents containing at least one of amino, mercapto, or epoxy groups, and examples may include γ-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, etc. Silane coupling agents can inhibit the surface migration of siloxane compounds.
[0044] Examples of crosslinking agents (A-6) may include diethanolamine, 1,4-butanediamine, 1,6-hexamethylenediamine, triethanolamine, diisopropanolamine, ethylene glycol, butanediol, 1,6-hexanediol, 1,4-cyclohexanediol, low molecular weight epoxides, adducts of polyfunctional amines or alcohols, and various low molecular weight polyfunctional hydroxyl or amine compounds. Low molecular weight can refer to a weight-average molecular weight of 50 to 500.
[0045] A) The weight-average molecular weight of thermoplastic polyurethane can be from 80,000 g / mol to 200,000 g / mol.
[0046] When A) thermoplastic polyurethane contains polyether polyols as the main component, its affinity for metal particles and weather resistance can be further improved. When A) thermoplastic polyurethane contains polyester polyols as the main component, it can exhibit better resistance to repeated bending fatigue, but may require the inclusion of hydrolysis inhibitors as described below.
[0047] Thermoplastic polyurethanes can have Shore A hardness ranging from 59 to 92, for example, 60 to 90. If the Shore A hardness is less than 59, the molded body to which the composition is applied may break under tension due to insufficient mechanical properties, and may have difficulty maintaining its shape during extrusion molding, leading to reduced productivity. On the other hand, if the Shore A hardness exceeds 92, insufficient elasticity and flexibility of the material may reduce resistance to repeated bending fatigue, excessive plasticizer may be required due to difficulty in mixing, and separation of metal particles in the molded body to which the composition is applied may occur.
[0048] A) Examples of commercially available thermoplastic polyurethane products may include trade names such as Desmopan 9370A (Covestro), Elastollan 1180A 10 (BASF), and Estane 58245 (Lubrizol).
[0049] B) Plasticizers can be liquid or solid materials capable of increasing the flexibility and processability of the composition. Plasticizers can exist in the liquid phase at room temperature of 23°C to 25°C.
[0050] B) Plasticizers may include at least one of alkane compounds, cycloalkane compounds, olefin compounds, aromatic compounds, or combinations thereof, and may include, for example, cycloalkane compounds (oils) or olefin compounds (oils).
[0051] Based on 100 parts by weight of A) thermoplastic polyurethane, compositions for vehicle wheel components may contain B) 1 to 30 parts by weight, for example 7 to 28 parts by weight of a plasticizer. If the amount of plasticizer is less than 1 part by weight, the surface shape may be poor due to insufficient flexibility, the interfacial reactivity between the metal particles and the polymer components may be insufficient, and cracking may easily occur due to repeated bending. On the other hand, if the amount of plasticizer exceeds 30 parts by weight, plasticizer migration to the polymer surface may occur predominantly, adhesiveness may occur during blending, and the shape may be poor during extrusion molding.
[0052] B) Examples of commercially available plasticizers may include trade names such as Shellflex371 (Shell), Synfluid 6cSt (Chevron), etc.
[0053] C) The metal particles may include metals with corrosion resistance and high density and specific gravity, and examples may include stainless steel, titanium, nickel, chromium, zinc, copper, nickel-copper alloys (Monel), nickel-chromium alloys (Inconel), nickel-molybdenum-chromium alloys (Hastelloy), etc. In some embodiments, at least one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, or combinations thereof is included.
[0054] In C) metal particles, SUS304 can be used as austenitic stainless steel, and SUS309, 310, 314, 330, 303, 316, 317, etc. can be used as needed.
[0055] In C) metal particles, SUS430 can be used as ferritic stainless steel, and SUS444, 434, 436, 405, 409, etc. can be used as needed.
[0056] In C) metal particles, SUS630 can be used as martensitic stainless steel, and SUS631, etc. can be used as needed.
[0057] C) The metal particles may be a mixture of a first particle with a relatively small size, a second particle with a medium size, and a third particle with a relatively large size. The size (D50) of the first particle may be from 10 μm to 50 μm, the size (D50) of the second particle may be from 30 μm to 120 μm, and the size (D50) of the third particle may be from 120 μm to 150 μm. In this document, D50 may be the particle size corresponding to 50% of the particle size-weight distribution by cumulative weight.
[0058] C) The metal particles may include a first particle and a second particle. The weight ratio of the first particle to the second particle may be 3:7 to 7:3.
[0059] When C) the metal particles include a first particle, a second particle and a third particle, based on 100 parts by weight of the second particle, 50 to 150 parts by weight of the first particle and 50 to 150 parts by weight of the third particle can be mixed.
[0060] C) The size (D50) of the metal particles can be from 1 μm to 150 μm, for example, from 30 μm to 120 μm. When the particle size falls within the above range, high dispersibility can be ensured, these particles can be loaded into thermoplastic polyurethane at a high filling rate, and the desired mechanical properties can be obtained.
[0061] C) The density of the metal particles can be 6 g / cm³. 3 Or even higher, for example, 6.5 g / cm³ 3 Or larger, and 10g / cm 3 Or even smaller. Density can correspond to tap density and can be measured by minimizing the void ratio using a typical tap density meter. The apparent density of metal particles can be 4 g / cm³. 3 Up to 8g / cm 3 .
[0062] C) The metal particles can have irregular shapes, plate shapes, spherical shapes, etc. In some embodiments, the metal particles can have a spherical shape.
[0063] Based on 100 parts by weight of thermoplastic polyurethane, compositions for vehicle wheel components may contain 400 to 1,680 parts by weight, for example 600 to 1,650 parts by weight of C) metal particles. If the amount of metal particles is less than 400 parts by weight, the molded body to which the composition is applied may require a larger volume, and noise may be generated when applied to a vehicle wheel. On the other hand, if the amount of metal particles exceeds 1,680 parts by weight, poor mixing may occur during composition mixing and molded body production, metal particle segregation may occur, and the interfacial reactivity between the metal particles and the thermoplastic polyurethane may be insufficient, resulting in reduced resistance to repeated bending fatigue.
[0064] As needed, compositions for vehicle wheel components may optionally include hydrolysis inhibitors or oxidation inhibitors. Examples of hydrolysis inhibitors or antioxidants may include additives containing hydroxycitric acid (trade names Stabaxol I, P200, etc.), additives containing urethane bonds (trade names Stabaxol P100, Ucarlink XL-29SE, etc.), additives containing epoxy groups (oxazolidine, trade name Loxiol G59, etc.), additives containing phenol groups (trade names Irganox 1010, 1076, 245, etc.), additives containing phosphate groups (trade names Irgafox 168, Ultranox 626, etc.), additives containing hydroxylamine groups (trade names Tinuvin 770, 765, etc.), carbodiimide compounds, etc. Based on 100 parts by weight of thermoplastic polyurethane, a hydrolysis inhibitor may be added in an amount from 0.5 parts by weight to 5 parts by weight. When the amount falls within the above weight range, the hydrolysis inhibitor can be easily dispersed, and its function can be effectively applied.
[0065] The composition for use in vehicle wheel components may further include acid acceptors, vulcanization accelerators, processing aids, anti-aging agents, fillers, etc. Acid acceptors may include metal oxides, metal hydroxides, etc. Vulcanization accelerators may include quaternary ammonium salts, quaternary phosphonium salts, etc. Anti-aging agents may include diphenylamine derivatives, phenylenediamine derivatives, etc. Processing aids may include stearic acid, zinc oxide, etc. Fillers may include carbon black, kaolin, talc, diatomaceous earth, etc.
[0066] The apparent density of the composition used for vehicle wheel components can be 3 g / cm³. 3 Up to 8.5 g / cm 3 .
[0067] The composition for vehicle wheel components can be produced into a molded body by extrusion molding, and the molded body can have good values of the parameters related to bending fatigue resistance, hydrolysis resistance, salt water resistance (corrosion resistance) and weather resistance as described below.
[0068] molded body
[0069] Another aspect of this disclosure relates to a molded body obtained by extruding a composition used in vehicle wheel components.
[0070] The molded body may have a component weight ratio substantially similar to that of the composition described above for vehicle wheel components, and some plasticizer components may evaporate due to extrusion molding in the composition for vehicle wheel components. For example, the molded body may contain A) 100 parts by weight of thermoplastic polyurethane, B) 0.5 to 28 parts by weight of plasticizer, and C) 400 to 1,680 parts by weight of metal particles, and may have a content of 3.2 g / cm³. 3Up to 8g / cm 3 The density. Density can correspond to apparent density.
[0071] Extrusion molding may include heating a composition for vehicle wheel components to a predetermined temperature, extruding the heated product, and post-processing the extruded product.
[0072] In extrusion molding, the heating temperature can be between the glass transition temperature and the melting point of the thermoplastic polyurethane, or a temperature range around the melting point, such as 130°C to 180°C.
[0073] In extrusion molding, extrusion can be performed to form an extrudate with a desired shape.
[0074] In extrusion molding, post-processing may include cutting the extrudate, printing the surface, etc.
[0075] Extrusion molding can be performed using an extruder, which includes: a hopper into which raw material is introduced; a barrel configured to communicate with the hopper and including a flow space for the raw material; an agitator configured to agitate and move the raw material in the flow space; a heater configured to heat the flow space; and a discharge die configured to communicate with the flow space. Furthermore, prior to extrusion molding, Banbury mixers, kneaders, mixing rollers, etc., can be used to mix, blend, and disperse compositions for vehicle wheel components.
[0076] When subjected to fewer than 50 bending tests, the molded body may remain substantially uncracked or fractured. In this context, a crack can be a gap or split with a width of 50 μm or greater.
[0077] [Bending Test]
[0078] A test is performed by bending a plate-shaped molded body with a width of 23 mm, a length of 100 mm, and a thickness of 4.5 mm for 2 seconds until one end in the longitudinal direction and the remaining end touch each other, and then returning it to its initial state. The longitudinal direction refers to the longer of the horizontal or vertical direction of the molded body.
[0079] Even when subjected to 70 or 100 bending tests, the molded body can remain virtually uncracked or unbroken.
[0080] After treatment at 120°C and 100% relative humidity for 48 hours according to MS220-17(4.6), the molded body may not crack or break.
[0081] According to MS 600-35(7.11) and IEC 60068-2-52, after spraying with brine at 35°C, a brine concentration of 5 wt%, and a pH of 7 for 720 hours, the molded body can have a surface corrosion area of 0.1 vol% or less and can be substantially non-corroded. The brine can contain sodium chloride or calcium chloride at the above-mentioned concentrations.
[0082] According to MS210-06, SAE J2527, and ASTM D7869, even after repeating one cycle (including using 340nm UV light at 0.75W / m), 2 Irradiate for 120 minutes, then spray with water in the dark for 60 minutes, until the UV irradiance reaches 2,500 kJ / m². 2 The molded body can be substantially free from discoloration, migration and whitening, and the changes in the L, a, and b values of the CIE Lab chromaticity coordinates measured after UV irradiation under the above conditions can be within ±5% of the values before irradiation.
[0083] The molded body can be applied to parts or components requiring the above-mentioned properties, and can be used as a wheel component of a vehicle, and as a wheel balance weight. When used as a wheel balance weight, the molded body can be formed as follows: Figure 1 The rollable strip shape is shown. Furthermore, individual films can be further attached to one side and / or the remaining side of the molded body, and adhesive films and release films can be attached to the molded body.
[0084] A better understanding of this disclosure can be obtained through the following embodiments and comparative examples. However, these embodiments should not be construed as limiting the technical spirit of this disclosure.
[0085] Example 1
[0086] A composition comprising A) 100 parts by weight of a polyether polyol thermoplastic polyurethane elastomer with a Shore A hardness of 60, B) 15 parts by weight of a naphthenic oil as a plasticizer, and C) 1,415 parts by weight of ferritic stainless steel powder (30-120 μm) as metal particles is mixed in a heated mixer and extruded in a heated extruder to produce a molded body. Mixing and extrusion are carried out at a temperature of 130-180°C.
[0087] Example 2
[0088] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) a plasticizer was used in an amount of 19 parts by weight, and C) metal particles were used in an amount of 1,650 parts by weight.
[0089] Example 3
[0090] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 80 was used, B) a plasticizer was used in an amount of 25 parts by weight, and C) metal particles were used in an amount of 1,100 parts by weight.
[0091] Example 4
[0092] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 90 was used, B) a plasticizer was used in an amount of 28 parts by weight, and C) metal particles were used in an amount of 900 parts by weight.
[0093] Example 5
[0094] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) a plasticizer was used in an amount of 7 parts by weight, and C) metal particles were used in an amount of 600 parts by weight.
[0095] Example 6
[0096] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used in which polyether polyol polyurethane elastomer and polyester polyol polyurethane elastomer were mixed in a weight ratio of 5:5; C) metal particles were used in an amount of 1,500 parts by weight; and 1 part by weight of hydrolysis inhibitor was further used.
[0097] Comparative Example 1
[0098] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 58 was used, B) a plasticizer was used in an amount of 13 parts by weight, and C) metal particles were used in an amount of 1,380 parts by weight.
[0099] Comparative Example 2
[0100] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 93 was used, B) a plasticizer was used in an amount of 35 parts by weight, and C) metal particles were used in an amount of 850 parts by weight.
[0101] Comparative Example 3
[0102] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) a plasticizer was used in an amount of 28 parts by weight, and C) metal particles were used in an amount of 1,700 parts by weight.
[0103] Comparative Example 4
[0104] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) the plasticizer was omitted, and C) metal particles were used in an amount of 1,300 parts by weight.
[0105] Comparative Example 5
[0106] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) the plasticizer was omitted, and C) metal particles were used in an amount of 380 parts by weight.
[0107] See Example 6
[0108] The molded body was produced in the same manner as in Example 1, except that: A) a polyester polyol thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used; B) a plasticizer was used in an amount of 7 parts by weight; and C) metal particles were used in an amount of 600 parts by weight. No separate hydrolysis inhibitor was added to the raw materials.
[0109] Comparative Example 7
[0110] The molded body was produced in the same manner as in Example 1, except that: A) a thermoplastic polyurethane elastomer with a Shore A hardness of 70 was used, B) a plasticizer was used in an amount of 35 parts by weight, and C) metal particles were used in an amount of 1,700 parts by weight.
[0111] The conditions for the embodiments, comparative examples, and reference examples are briefly shown in Table 1 below.
[0112] [Table 1]
[0113]
[0114] TPU: Thermoplastic polyurethane elastomer
[0115] Test Example - Measurement of Bending Fatigue Resistance and Density (Specific Gravity)
[0116] like Figure 2 As shown, the bending fatigue resistance of the molded bodies produced in the Examples, Comparative Examples, and Reference Examples was measured by the following bending test, and their apparent density (23°C) was measured using a densitometer. The results are shown in Table 2 below. Figure 3 middle.
[0117] [Bending Test]
[0118] The test involves repeatedly bending a plate-shaped molded body with a width of 23 mm, a length of 100 mm, and a thickness of 4.5 mm at a temperature of 23°C and a relative humidity of 50% for 2 seconds, so that one end in the longitudinal direction and the remaining end come into contact with each other, and then restoring it to its initial state for one cycle until cracking occurs.
[0119] Test Example - Measurement of Hydrolysis Resistance
[0120] According to MS220-17(4.6), molded bodies produced in the Examples, Comparative Examples, and Reference Examples were treated for 48 hours at 120°C and 100% relative humidity, and then the presence or absence of cracking and fracture was measured. The results are shown in Table 2 below, and some results are shown in... Figure 4 middle.
[0121] Test Example - Measurement of Salt Water Resistance
[0122] The surface corrosion status of molded bodies produced in the Examples, Comparative Examples and Reference Examples was measured by spraying with brine for 720 hours at a temperature of 35°C, a brine concentration of 5 wt%, and a pH of 7, in accordance with MS 600-35(7.11) and IEC 60068-2-52, and the results are shown in Table 2 below.
[0123] Test Example - Measurement of Weather Resistance
[0124] According to MS210-06 and SAE J2527, by repeating one cycle (including using 340nm ultraviolet light at 0.75W / m) 2 The molded bodies produced in the Examples, Comparative Examples, and Reference Examples were treated with UV irradiation for 120 minutes, followed by spraying with water in the dark for 60 minutes, until the UV irradiation reached 2,500 kJ / m². 2 Then, its discoloration, migration, and whitening were measured, and the results are shown in Table 2 below.
[0125] [Table 2]
[0126]
[0127]
[0128] Referring to the table, Examples 1 to 6 exhibit good composition mixing and molded body extrusion appearance, as well as satisfactory flexural fatigue resistance, density, hydrolysis resistance, salt water resistance, and weather resistance at appropriate levels.
[0129] In Comparative Example 1, which uses TPU with a slightly lower Shore A hardness, cracking occurred due to insufficient mechanical properties when the bending test was repeated 40 times.
[0130] In Comparative Example 2, which uses TPU with a slightly higher Shore A hardness, microcracks occurred at the edges during the extrusion molding process due to insufficient mixing and flexibility, resulting in an undesirable appearance.
[0131] In Comparative Example 3, the use of excessive metal particles caused poor mixing and separation of the metal particles. Furthermore, due to insufficient interfacial reactivity between the metal particles and TPU, cracking occurred after 40 repeated bending tests.
[0132] In Comparative Example 4, which did not use plasticizers, cracking occurred when the bending test was repeated 45 times due to insufficient interfacial reactivity between the metal particles and TPU.
[0133] In Comparative Example 5, the density (specific gravity) of the molded body was unsatisfactory for the wheel balance block product conditions. If the density were 3 g / cm³... 2 If it is smaller, a larger relative volume for the required specific gravity may result in noise in the wheel.
[0134] In Reference Example 6, which uses polyester polyol-based TPU without hydrolysis inhibitors, cracking and breakage occurred during hydrolysis resistance measurements, and discoloration occurred during weather resistance evaluation due to surface blooming.
[0135] In Comparative Example 7, which used excessive plasticizer, a sticky material was generated in the mixer during mixing, and plasticizer migration occurred, causing discoloration during the weather resistance evaluation.
[0136] As is apparent from the foregoing, the compositions according to embodiments of the present disclosure can be readily molded, and the molded body using the compositions can exhibit excellent adhesion to the curved surfaces of vehicle wheels.
[0137] Furthermore, molded bodies using the compositions according to embodiments of this disclosure exhibit fatigue resistance to repeated bending that occurs during mass production or balancing operations, and are able to alleviate the problem of reduced productivity.
[0138] Furthermore, when applied to wheels, the molded body using the composition according to embodiments of this disclosure can reduce the defect rate by 50% or more compared to metal products.
[0139] Furthermore, the molded body of the composition according to the embodiments of the present disclosure can be precisely balanced in small units of 0.5g, thereby achieving a low wheel balance error rate and minimizing noise generation and interference with the brake caliper in vehicle driving mode.
[0140] Furthermore, molded bodies using the compositions according to embodiments of this disclosure exhibit excellent hydrolysis resistance under conditions such as hot summers, high temperatures, and high humidity, resistance to salt water such as sodium chloride and calcium chloride, and good weather resistance to ultraviolet light. Therefore, the molded bodies can demonstrate durability suitable for vehicle wheel components subjected to prolonged exposure to external environments.
[0141] The effects of this disclosure are not limited to those described above. It should be understood that the effects of this disclosure include all effects that can be inferred from the description herein.
[0142] Although specific embodiments of this disclosure have been described, it should be understood by those skilled in the art that this disclosure may be embodied in other specific forms without altering its technical spirit or essential characteristics. Therefore, the above embodiments should be understood as non-limiting and illustrative in any way.
Claims
1. A composition for a vehicle wheel component, comprising: 100 parts by weight of thermoplastic polyurethane, 1 to 30 parts by weight of plasticizer, and 400 to 1,680 parts by weight of metal particles, in, The composition has a concentration equal to or greater than 3 g / cm³. 3 The density of the thermoplastic polyurethane is such that the thermoplastic polyurethane has a Shore A hardness in the range of 59 to 92.
2. The composition according to claim 1, wherein, The vehicle wheel component is a wheel balance block.
3. The composition according to claim 1, comprising: 7 to 28 parts by weight of the plasticizer; and 600 to 1,650 parts by weight of the metal particles, in, The thermoplastic polyurethane has a Shore A hardness of 60 to 90.
4. The composition according to claim 1, wherein: The thermoplastic polyurethane includes a thermoplastic polyurethane elastomer, and The thermoplastic polyurethane elastomer is obtained by reacting at least one of polyester polyols, polyether polyols or combinations thereof, diisocyanate compounds, compounds containing hydrogen and acid functional groups capable of reacting with isocyanates, hydroxyl-containing siloxane compounds, silane coupling agents and crosslinking agents.
5. The composition according to claim 4, wherein, When the thermoplastic polyurethane elastomer contains a polyester polyol-derived component, the composition further contains a hydrolysis inhibitor.
6. The composition according to claim 1, wherein, The thermoplastic polyurethane has a weight-average molecular weight in the range of 80,000 to 200,000 g / mol.
7. The composition according to claim 1, wherein, The plasticizer includes at least one of alkane compounds, cycloalkane compounds, olefin compounds, aromatic compounds, or combinations thereof.
8. The composition according to claim 1, wherein, The metal particles have a density equal to or greater than 6 g / cm³. 3 The density.
9. The composition according to claim 1, wherein, The metal particles include at least one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, or combinations thereof.
10. The composition according to claim 1, wherein, The size D50 of the metal particles is in the range of 1 μm to 150 μm.
11. The composition according to claim 1, wherein: The metal particles include a first particle, a second particle, and a third particle. The size D50 of the first particle is in the range of 10 μm to 50 μm. The size D50 of the second particle is in the range of 30 μm to 120 μm, and the size D50 of the third particle is in the range of 120 μm to 150 μm.
12. The composition according to claim 1, further comprising at least one of an acid acceptor, a vulcanization accelerator, a processing aid, an anti-aging agent, a filler, or a combination thereof.
13. A molded body comprising: Thermoplastic polyurethane, Based on 100 parts by weight of the aforementioned thermoplastic polyurethane, 400 to 1,680 parts by weight of metal particles, and Plasticizer, in, The molded body has a content equal to or greater than 3.2 g / cm³. 3 The density of the thermoplastic polyurethane is such that the thermoplastic polyurethane has a Shore A hardness in the range of 59 to 92.
14. The molded body according to claim 13, wherein, When subjected to 50 bending tests, the molded body did not crack or break. The bending test is a test in which a plate-shaped molded body with a width of 23 mm, a length of 100 mm and a thickness of 4.5 mm is bent for 2 seconds at a temperature of 23°C and a relative humidity of 50%, such that one end and the remaining end in the longitudinal direction come into contact with each other, and then returns to its initial state.
15. The molded body according to claim 13, wherein, After being treated at 120°C and 100% relative humidity for 48 hours, the molded body did not crack or break.
16. A wheel balance block comprising the molded body of claim 13.
Citation Information
Patent Citations
Cotton-harvester
US310314A